Rational design of three bifunctional MOFs for photocatalysis degradation and selective adsorption of wastewater organic dyes removal. (15th November 2020) - Zhang, Xiaoyin; Zong, Ziao; Zhang, Xia; Zhang, Dongmei; Luo, Qingdan; Bi, Caifeng; Fan, Yuhua
Graphical abstract: Highlights: Three MOFs based on based on transition metals have been synthesized. The title MOFs exhibit both good photocatalytic degradation and adsorption for organic dyes removal capability for waste water treatment. The tentative mechanism has been discussed. Abstract: Three metal–organic frameworks (MOFs) based on transition metals, namely{[Cd(HL)(tib)(H2 O)]·1·.5H2 O}}n (1), {[Co3 (L)2 (tib)2 ]·4H2 O}n (2), [Cu(L)(3, 5-bibp)]n (3) (H3 L = 4-(3, 5-dicarboxylatobenzyloxy)benzoic, tib = 1, 3, 5-tris(1-imidazolyl)benzene and 4, 4′-bibp = 4, 4′-bis(imidazol-1-yl)biphenyl) have been designed and successfully synthesized under solvothermal conditions. These three compounds were characterized by single crystal X-ray diffraction, elemental analysis, IR spectra, powder X-ray diffraction (PXRD), thermogravimetric analysis(TGA) and electrochemical studies. Single crystal X-ray diffraction analysis reveals that compound 1 possesses a 2-nodal (3, 5)-connected hms topology framework with the point symbol (6 3 ·6 9. 8), compound 2 unprecedented 3-nodal (8, 8, 11)-connected 3D framework with a (3 7 ·4 12 ·5 9 ) (3 8 ·4 13 ·5 7 ) (3 9 ·4 19 ·5 23 ·6 4 ) topology, while compound 3 displays a 3D 4-connected sql topology. The electrochemical studies for compound 2 and 3 have been discussed. Photocatalytic degradation and adsorption for organic dyes removal from wastewater using three compounds have been investigated. Significantly, all of the three compounds show good photocatalytic activities for MB and selective adsorption capacity for CR.